Preliminary Results on Aquatic Insects in the Me Linh Station for Biodiversity, Vinh Phuc Province - Hieu, Nguyen Van; Vinh, Nguyen Van (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4DO - 10.25073/2588-1140/vnunst.4696, 2017)
An intensive field survey on aquatic insects of Me Linh Station for Biodiversity in Vinhphuc province was conducted in December 2015. Specimens were collected at 8 different sites and aquatic insects were collected both quantitatively by Surber net and qualitatively by hand net, pond net. As a result, a total of 110 aquatic insect species belonging to 98 genera, 49 families and 9 orders were recognized. Among these, the order Ephemeroptera had the highest species number with 26 species, followed by Odonata with 25 species, Trichoptera with 18 species, Coleoptera with 15 species, Hemiptera with 11 species, Diptera with 9 species. Lepidoptera, Plecoptera and Megaloptera had the lowest of species number, represented by 3 species of Lepidoptera, 2 species of Plecoptera and 1 species of Megaloptera. Besides, the quantitative analysis results and the functional feeding groups were provided.